Service quality: beyond cognitive assessment - Edvardsson, Bo (Managing service quality, 2005)
Purpose - The aim of this article is to contribute to widening the scope of service quality by focusing on dimensions beyond cognitive assessment. The focus is on the role of customers' emotions in service experiences.Design methodology approach - The article first discusses the service concept and implications for service quality. It then focuses on the role of customer experiences, and then discusses the role of emotions in service quality.Findings - The paper presents six propositions related to service experiences when consuming services and the role of emotions in customer-perceived service quality.Originality value - The paper contributes to widening the scope of service quality by focusing on dimensions beyond cognitive assessment.